Delaminated MXene for efficient chromium removal via photocatalytic proces / Nur Shafiqah Jamaluddin - Jamaluddin, Nur Shafiqah (2022)
Hexavalent chromium (Cr(VI)) is considered a major hazardous heavy metal in water bodies that can cause severe effects to human health and the environment. Over the years, myriad photocatalyst have been used to remove Cr(VI) from wastewater. However, broad bandgap energy and high electron recombination rate of these photocatalysts have limit their photocatalytic performance. Therefore, an efficient photocatalyst for Cr(VI) removal in wastewater is strongly demanded. In this study, the structural, physicochemical and thermal properties of delaminated MXene have been successfully investigated.